Berlin Biennale for Contemporary Art : The Present in Drag - David Torro (curator); Lauren Boyle (curator); Marco Rose (curator); Solomon Chase (curator); Berlin Biennale for Contemporary Art (Distanz Verlag; KW Institute for Contemporary Art; German Federal Cultural Foundation, 2016)
Curated by the New York collective DIS, the 9th Berlin Biennale is a platform for collaborative ventures, ideas, catastrophes, and extremes. It seeks to materialize the paradoxes that increasingly define the world of 2016: the virtual as the real, nations as brands, people as data, culture as capital, wellness as politics, happiness as GDP, and so on. "The Present in Drag" is published as a companion volume to the 9th Berlin Biennale for Contemporary Art. Providing information on the works shown in the exhibition, it also includes contributions by Roe Ethridge, Simon and Daniel Fujiwara, Boris Groys, Katja Novitskova, Chus Martínez, Bjarne Melgaard, Sean Patrick Monahan, Sabine Reitmaier, McKenzie Wark, and others. Contributors: Rob Horning; Chus Martinez; Natasha Stagg; Boris Groys; Mckenzie Wark; Meredith Meredith; Sean Monahan; Ingo Niermann; Oleg Fonaryov; Sean Raspet; Rem Koolhaas; Hans Ulrich Obrist; Harry Met Sally; Simon and Daniel Fujiwara; Roe Ethridge, Babak Radboy; Chris Kraus; Bjarne Melgaard; Jason Nocito; Antoni Abad; Halil Altindere; Ei Arakawa; Dan Poston; Stefan Tcherepnin; Korakrit Arunanondchai; Alex Gvojic; atelier le balto; Armen Avanessian; Alexander Martos; Christopher Roth; Will Benedict; Julien Ceccaldi Centre for Style; Brody Condon; CUSS Group; Kathleen Daniel; Debora Delmar Corp.; Simon Denny; Cecile B. Evans; Nicolas Fernandez; Lizzy Fitch; Ryan Trecartin; Simon Fujiwara; GCC; Guan Xiao; Calla Henkel/ Max Pitegoff; Camille Henrot; Yngve Holen; Alexa Karolinski; Ingo Niermann; Josh Kline; Korpys; Loffler; Nik Kosmas; Christopher Kulendran Thomas; M/L Artspace; Shawn Maximo; Katja Novitskova; Trevor Paglen; Jacob Appelbaum; Juan Sebastian Pelaez; Adrian Piper; Alexandra Pirici; Josephine Pryde; Puppies Puppies; Jon Rafman; Timut Si-Qin; Lucie Stahl; Hito Steyerl.
English; German
Keywords: N4390-5098 Exhibitions